2012
DOI: 10.1248/bpb.35.568
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects by Intake of <i>Euphausiacea pacifica</i> on High-Fat Diet-Induced Obesity

Abstract: Obesity is a major health problem showing increased incidence in developed and developing countries. We examined the effect of Euphausia pacifica (E. pacifica) (Pacific Krill) on high-fat diet (HFD)-induced obesity in C57BL/6 mice. No significant differences were observed in average food intake between the HFD and HFD with E. pacifica group, or the low-fat diet (LFD) and LFD with E. pacifica group for 18 weeks. The increased ratio of body weight in the HFD containing E. pacifica group was significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…This ratio did not change in the current study, suggesting that TC and LDL-C increase might not be detrimental. These results support findings from our previous study which demonstrated an incremental increase [ 8 ], as well as other studies showing no change [ 6 , 7 , 36 ], in plasma concentrations of total and LDL cholesterol in normolipidemic participants after krill oil supplementation. Both LPL and HPL krill oils were well tolerated by the participants and caused no adverse effects which shows the safety nature of krill oil.…”
Section: Discussionsupporting
confidence: 92%
“…This ratio did not change in the current study, suggesting that TC and LDL-C increase might not be detrimental. These results support findings from our previous study which demonstrated an incremental increase [ 8 ], as well as other studies showing no change [ 6 , 7 , 36 ], in plasma concentrations of total and LDL cholesterol in normolipidemic participants after krill oil supplementation. Both LPL and HPL krill oils were well tolerated by the participants and caused no adverse effects which shows the safety nature of krill oil.…”
Section: Discussionsupporting
confidence: 92%
“…Although krill oil supplementation has demonstrated hypolipidemic activity in some studies, this effect is found to be more pronounced with participants with hyperlipidemia [ 11 , 36 , 38 ]. Similar results were found in previous studies with normolipidemic participants in whom there was no effect on serum lipids [ 10 , 17 , 39 ]. Reduction of serum TG by n-3 PUFA also depends on their baseline concentrations [ 36 , 38 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although lipids are major bioactive compounds in krill oil, we found in a previous study that a watersoluble extract from Pacifi c krill could suppress weight gain in mice caused by a high fat diet. The levels of triglycerides in the livers of mice given a water-soluble extract from Pacifi c krill decreased ( 32 ).…”
Section: Triglyceride Staining and Quantifi Cationmentioning
confidence: 99%